THE INFLUENCE OF GREEN MARKETING, PRODUCT QUALITY, AND PRICE TOWARDS CUSTOMER SATISFACTION AT RED HERBS TOMOHON - Wongkar, Naftalia; Tielung, Maria V. J.; Rumokoy, Lawren J. (Universitas Sam Ratulangi, 2024)
One of the businesses that is growing rapidly and feeling the tight competition is the business in the food sector or more known as culinary industry. This study aims to identify whether there is an influence between green marketing, product quality, and price towards customer satisfaction at Red Herbs Tomohon. Type of research in this study is quantitative. Non-probability has used in this research. The non-probability sampling technique approach in this study was purposive sampling. The results of this research show that Green Marketing, Product Quality, and Price on customer satisfaction have a positive influence simultaneously. The results of this research show that green marketing on customer satisfaction has a positive influence partially. The results of this research show that product quality on customer satisfaction has a positive influence partially. The results of this research in the previous chapter show that price on customer satisfaction has a positive influence partially. Green Marketing, Product Quality, and Price has a positive influence towards customer satisfaction at Red Herbs Tomohon through the indicators of Customer Satisfaction such as loyalty, satisfaction, the willingness to recommend the product. Keyword: Green Marketing, Product Quality, Price, Customer Satisfaction